APLIKASI PENERAPAN MOTIF BATIK KAWUNG PADA SEPATU KULIT BOOT - Lisa Andri Ana; Kusmadi (Canthing, 2022)
The development of an increasingly modern and advanced era makes designs or models experience rapid development. In meeting the times, both in terms of design and quality of workmanship. the technique of applying ornaments will increase the selling value of a batik leather shoe product which is still rare for batik leather shoe products on the market. The concept of making shoe works is taken from the form of the kawung batik motif, namely an ancient batik motif consisting of an arrangement of elliptical (oval) shapes that have four equal sides. exploration stage, design stage, and embodiment. Application of kawung motifs on leather as shoe decoration using batik techniques. Batik techniques on leather media are almost the same as batik techniques applied to cloth media. The development of the kawung batik motif in functional works such as women's shoes is expected to be a new breakthrough to create other functional works that take the theme of tradition, especially the tradition of the archipelago into contemporary fashion works. Keywords: Kawung Batik Motif, Leather Shoes